The assessment of international tourists' perception and revisit intention towards Thai government's beach clean-up policy : A case study of patong beach, Phuket - Pattma Korkamnertkawin (Prince of Songkla University, 2018)
Thesis (M.B.A., Hospitality and Tourism Management) Prince of Songkla University, 2015